2017
DOI: 10.1111/vru.12558
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radiography and computed tomography to evaluate fractures of the canine tarsus

Abstract: Detection and accurate classification of traumatic tarsal fractures are important for identifying cases requiring surgical intervention. The aim of this prospective, experimental, methods comparison study was to directly compare the accuracy, sensitivity, and specificity of tarsal computed tomography (CT), ten-view and two-view digital radiographs for detecting traumatic fractures of the canine tarsus. The working hypothesis was that tarsal fractures would be detected with higher accuracy, sensitivity, and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 18 publications
(38 reference statements)
0
13
2
Order By: Relevance
“…2,10,12,14,20 Partial tarsal arthrodesis, which was used commonly in this case series, has been associated with complications, particularly those relating to the regional soft tissue structures (bandage sores, incision dehiscence, and infection). 5,31,32 These complications would be expected to be less commonly encountered after primary fixation; however, our results do not provide evidence to support a difference in complications or outcomes between these procedures. Findings described in previous literature comparing reconstruction and arthrodesis lead us to believe that it is possible that this finding is a type II error and that, with a larger cohort, we may find a more significant difference in complications between fixation groups.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…2,10,12,14,20 Partial tarsal arthrodesis, which was used commonly in this case series, has been associated with complications, particularly those relating to the regional soft tissue structures (bandage sores, incision dehiscence, and infection). 5,31,32 These complications would be expected to be less commonly encountered after primary fixation; however, our results do not provide evidence to support a difference in complications or outcomes between these procedures. Findings described in previous literature comparing reconstruction and arthrodesis lead us to believe that it is possible that this finding is a type II error and that, with a larger cohort, we may find a more significant difference in complications between fixation groups.…”
Section: Discussioncontrasting
confidence: 68%
“…With the high prevalence of soft tissue complications that were present in this study and have been described after similar tarsal fixations, our results provide evidence that postoperative antibiotic administration should be carefully considered after Tc fixation. 5,31,32 Fractures that are associated with major complications were over 5 times more likely to have a poorer outcome score (5.64, 95% CI 0.69-53.84, P = .11); however, the CI here does include 1, so this result must be interpreted carefully. The authors consider it likely that, even though this report represents by far the largest sample of Tc fractures to date, the relatively small sample contributed to the failure of our results to reach statistical significance.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…11 The fact that the feline os penis is seen more frequently on CT images can be explained by the superior contrast resolution of CT when compared with radiography. 14 In the present study, cats showed, on average, a shorter cylindrical bone than in anatomical reports. 2,4 The reason for this difference is unclear, but the lower sample size could have influenced this difference.…”
Section: Discussioncontrasting
confidence: 45%
“…11 The fact that the feline os penis is seen more frequently on CT images can be explained by the superior contrast resolution of CT when compared with radiography. 14…”
Section: Discussionmentioning
confidence: 99%